Human CYP2E1-activated mutagenicity of dioxin-like PCBs 105 and 118—Experimental data consistent with molecular docking results. (15th May 2020) - Hu, Keqi; Yu, Hang; Li, Zihuan; Jin, Guifang; Jia, Hansi; Song, Meiqi; Liu, Yungang
Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants with human carcinogenicity. Many lower chlorinated and non-dioxin-like PCBs have been observed to be mutagenic following activation by human CYP2E1, while activation of dioxin-like (DL-) PCBs by this enzyme has never been evidenced. In this study, each DL-PCB was analyzed by molecular docking to human CYP2E1 protein for predicting a substrate interaction. All compounds demonstrated high affinities with the active site of human CYP2E1, binding energy being −8.7 ∼ −9.7 kcal/mol. However, most compounds demonstrated ligand-heme distances as ≥ 6.8 Å, while the values for 2, 3, 3′, 4, 4′- (PCB 105) and 2, 3′, 4, 4′, 5-pentachlorobiphenyl (PCB 118) were 5.3 and 5.4 Å, respectively (valid for electron transfer). Experimentally, both PCB 105 and 118 induced micronuclei in a V79-derived cell line engineered for expression of human CYP2E1 at low micromolar concentrations, while inactive or weakly positive in V79-Mz control cells; these effects were blocked or reduced by 1-aminobenzotriazole, a suicide CYP inhibitor. However, DL-PCBs 77, 81 and 126 were all negative in both cell lines. In a human hepatoma (C3A) cell line, PCB 105 and 118 induced micronuclei marginally, while with ethanol pretreatment (to stabilize CYP2E1) both compounds induced micronuclei efficiently, and co-exposure to trans -1, 2-dichloroethylene (a selective CYP2E1 inhibitor) led to clearly negative results with both compounds. Finally, both PCB 105 and 118 induced PIG-A gene mutations in C3A cells, which was blocked by trans -1, 2-dichloroethylene. In summary, in silico and experimental results consistently suggest that DL- PCBs 105 and 118 may be activated by human CYP2E1 for mutagenic activities.